Modelamiento y simulación de un robot clínico asistido por Ultrasonido 3D para mejorar el guiado de inserción de agujas en biopsia percutánea de mama - Jácobo Zavaleta, Sergio Augusto Antenor (2022)
This work describes a new concept of a 3D US image assisted clinical robot for percutaneous breast biopsy in order to improve the cancer diagnose by automated needle placement near the biopsy target that simplifies manual insertion procedure and alleviates radiologist’s fatigue. In this way, basic requirements for linking the procedures of Hand-Held Breast Ultrasound guided biopsy with an US image acquisition were first determined. Starting with a comparative analysis based on the advantages and disadvantages of image guided systems such as radiography and MRI. Which resulted in the proposal of a new clinical workflow for breast cancer diagnosis. Therefore, the robot kinematic chain was obtained by considering the woman breast as a workspace and its similarity with a 3D ABUS radial scanning. For the forward and inverse kinematic were used the screw axis based theory and a geometric-algebraic formulation, respectively. While the inverse and forward dynamic were described by the Newton-Euler algorithm and partial solutions in the rigid bodies dynamic equation, respectively. Moreover, using CAD models of the robot and other elements involved, it could be implemented a simulation environment in MATLAB-Simulink. Connected to a GUI for parameters entry as position and direction of needle insertion. Finally, the results showed a numerical and graphical verification of equations. Even, a visual one of the robot placement during two stages: Before a biopsy (preplacement) and after it (postplacement). In conclusion, it was possible to explore about using robotics for needle guidance in percutaneous breast biopsy, led by the recently accuracy of an ABUS 3D in whole breast tissue volumetric reconstruction.